RESILIENCE IN FEMALE OF GEN Z - Olivia Winda Ony Panjaitan (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The purpose of this study was to determine the level of resilience in female who are included in the category of generation Z (Gen-Z) group in Palangkaraya, Central Kalimantan. The research design used descriptive research. The sample in this study amounted to 129 respondents. Data collection techniques using a questionnaire adapted from Connor Davidson (2003). Based on the results of the study it was found that the level of resilience of female gendered Gen Z was categorized into three levels. At the high resilience level of 24%. Then those at the medium resilience level amounted to 59.7% and then at the low resilience level amounted to 16.3%. The results also show that in the resilience aspect, the control and factor aspect is found to have the highest value, while the aspects of trust in one's instinct, positive acceptance and spiritual influences have the lowest value in order. Overall, the results showed that female gendered Gen Z has the ability to adapt and cope with stress but still not maximized.